Design & analysis of diaphragm for MEMS based pressure sensors. (2022) - Thakar, Vishal C.; Patel, Bhakti N.; Karsh, P.K.
Abstract: The focus of this research is to design the diaphragm for Micro-electromechanical systems (MEMS) based pressure sensors. The major goal of this paper is to design and analyze the displacement of a diaphragm subjected to various external pressure. The diaphragm comes in variety of shapes, including square and rectangular. A comparative study of diaphragm with different shapes subjected to varying external pressures (0.2 MPa to 2 MPa) is presented. Diaphragm displacements as well as the developed stresses are studied. By comparing the square and rectangular diaphragms using classical theory, it found that the square diaphragm offers more displacement result as compared to the rectangular diaphragm. Maximum displacement and mises stress will occurs when applying pressure of 2 MPa. By using the non-classical theory also shows that a square diaphragm is good as compare to a rectangle diaphragm in terms of displacement.